Unexpected Radiation-Induced Aortic Wall Thickening Requiring Composite Graft Technique during Off-Pump Coronary Artery Bypass Grafting. (19th January 2017) - Redaelli, Paola; Gamba, Amando; Martino, Antonello Stefano; Triggiani, Michele
Abstract : Mediastinal radiation is commonly used to treat Hodgkin's and non-Hodgkin's lymphoma, lung and breast cancer. Cardiac complications after radiation therapy are well described, although rare. A large spectrum of injuries can occur, causing long term morbidity among survivors. We describe a case of post-actinic ascending aortic wall thickening that prevented saphenous vein proximal anastomosis and was successfully managed with aortic no-touch off-pump coronary artery bypass grafting (OPCAB), 25 years after radiation therapy for Hodgkin's lymphoma.